2019
DOI: 10.1029/2019ja027158
|View full text |Cite
|
Sign up to set email alerts
|

Eastward Propagating Second Harmonic Poloidal Waves Triggered by Temporary Outward Gradient of Proton Phase Space Density: Van Allen Probe A Observation

Abstract: Two wave packets of second harmonic poloidal Pc 4 waves with a wave frequency of~7 mHz were detected by Van Allen Probe A at a radial distance of~5.8 R E and magnetic local time of 13 hr near the magnetic equator, where plasmaspheric refilling was in progress. Proton butterfly distributions with energy dispersions were also measured at the same time; the proton fluxes at 10-30 keV oscillated with the same frequency as the Pc 4 waves. Using the ion sounding technique, we find that the Pc 4 waves propagated east… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 74 publications
(127 reference statements)
1
34
0
2
Order By: Relevance
“…The drift-bounce resonance condition ( r = m d +N b ) suggests that protons of 17.4 keV would experience an drift-bounce resonance (with N = 1) with the waves at intermediate pitch angles, ∼ 40 • and 140 • , if the waves have an m of ∼200 as suggested by Yamamoto et al, (2019; see Figure S2a and b). According to the conventional theory (e.g., Zhu et al, 2020), a 180 • phase shift is expected across either of the resonant pitch angles.…”
Section: Observationsmentioning
confidence: 90%
See 1 more Smart Citation
“…The drift-bounce resonance condition ( r = m d +N b ) suggests that protons of 17.4 keV would experience an drift-bounce resonance (with N = 1) with the waves at intermediate pitch angles, ∼ 40 • and 140 • , if the waves have an m of ∼200 as suggested by Yamamoto et al, (2019; see Figure S2a and b). According to the conventional theory (e.g., Zhu et al, 2020), a 180 • phase shift is expected across either of the resonant pitch angles.…”
Section: Observationsmentioning
confidence: 90%
“…Therefore, this set of wave parameters are reasonable. The wave number m is chosen as 170, in the m range suggested by Yamamoto et al (2019). As suggested by Figure S2a The simulation results are shown in the right column of Figure 3.…”
Section: Simulation and Interpretationmentioning
confidence: 99%
“…There have been a number of observational studies discussing the drift‐bounce resonance excitation of internally driven ULF waves. While there have been several studies which observed fundamental poloidal waves associated with the drift resonance (e.g., Dai et al, 2013; Yamamoto et al, 2018), previous observations overwhelmed the drift‐bounce resonance excitation of second harmonic poloidal waves (e.g., Le et al, 2017; Min et al, 2017; Oimatsu et al, 2018; Takahashi et al, 1985, 2018; Yamamoto et al, 2019). These observations suggest that internally driven ULF waves excited by the drift‐bounce resonance tend to have a poloidal polarization and propagate westward with high m numbers (| m | ~ 70–200) (e.g., Dai et al, 2013; Takahashi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One candidate for this interaction is ultra-low frequency (ULF) wave-particle interaction. Previous studies have proved that drift-bounce resonance, a primary type of ULF wave-particle interaction, can efficiently realize the energy exchange between waves and particles (e.g., Oimatsu et al, 2018Oimatsu et al, , 2020Ren et al, 2015Ren et al, , 2016Ren et al, , 2019Southwood & Kivelson, 1981Yamamoto et al, 2019;Yang et al, 2010;Zong et al, 2007Zong et al, , 2009Zong, Wang, et al, 2017). According to Southwood and Kivelson (1981), drift-bounce resonance occurs when the following condition is satisfied:  is particle bounce-averaged drift frequency, and b E  is particle bounce frequency.…”
Section: Introductionmentioning
confidence: 99%